SHALAT DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Muttaqin, Nurul (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2017)
The discussion of God and humanity in essence depends on the perspective and understanding of a religion, this is to emphasize the Absolute individuality of (God). The meaning of prayer is an effort to realize God and humans in spiritual, psychological, health, and mechanical experiences, or an attempt to unite mankind. Prayers indirectly educate and train themselves to be disciplined, clean, patient, and establish fellow Muslim relations so as to strengthen the sense of brotherhood. Some of the educational values ??contained in prayer are as follows: respecting time, intelligent spiritual, healthy mentality, human harmony, social sensitivity, creed as a recognition of the oneness of Allah Almighty and Muhammad's Messenger of Allah, spreading greetings as a reflection of social piety. Prayer is the wisest and most correct way for a Muslim to deal with problems and trials that happen to him so that anxiety does not become prolonged stress.